(12x+7)=(30x-4)

Simple and best practice solution for (12x+7)=(30x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x+7)=(30x-4) equation:


Simplifying
(12x + 7) = (30x + -4)

Reorder the terms:
(7 + 12x) = (30x + -4)

Remove parenthesis around (7 + 12x)
7 + 12x = (30x + -4)

Reorder the terms:
7 + 12x = (-4 + 30x)

Remove parenthesis around (-4 + 30x)
7 + 12x = -4 + 30x

Solving
7 + 12x = -4 + 30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30x' to each side of the equation.
7 + 12x + -30x = -4 + 30x + -30x

Combine like terms: 12x + -30x = -18x
7 + -18x = -4 + 30x + -30x

Combine like terms: 30x + -30x = 0
7 + -18x = -4 + 0
7 + -18x = -4

Add '-7' to each side of the equation.
7 + -7 + -18x = -4 + -7

Combine like terms: 7 + -7 = 0
0 + -18x = -4 + -7
-18x = -4 + -7

Combine like terms: -4 + -7 = -11
-18x = -11

Divide each side by '-18'.
x = 0.6111111111

Simplifying
x = 0.6111111111

See similar equations:

| 5a+9y=17 | | X^2-576=0 | | 1/5x+y=30 | | -28=-7x-2(-5x+23) | | 4(2-y)+3y=3(y-4) | | 16-8a=2a | | -11m+1=-10m+18 | | 8(7n-4)=-144 | | 8-n=3(2n-4) | | -11m+1=-10+18 | | -1/2(8x+2)+1/5(35x+10) | | 4b-7=20+4b | | (4u-5)(3+u)=0 | | 6b^2+23=11 | | 40/4=5x+2(-4x) | | 5/4(x+2)=3 | | 5w+41=3(w+9) | | 0.333333(x+3)+0.1666666(x-6)=x+3 | | (4x+1500)-(2x+1800)=0 | | -4/3x^2-19/18x-19/36=0 | | 2y+3=3(7+7) | | G+2(3+g)=4(g+1) | | 2=400/x | | (x+5y)dy=-(2x+3y)dx | | 7=5(x+5)-7x | | onethird(x+3)+onesixth(x-6)=x+3 | | 5xa-7a^2=2a^2+2ax | | -6x-3(7x-26)=-111 | | 4a-2a+11=6a-13 | | 9w+5= | | 5ax-7a^2=2a^2+2ax | | 8(-7+8v)=200 |

Equations solver categories